OPTIMATION OF FIRE EXTINGUISHMENT SYSTEMS IN X STATION CENTER OF CRUDE OIL AND GAS STORAGE - Aziz, Amiral; Andre Nugroho (Majalah Ilmiah Pengkajian Industri, 2021)
This paper discusses some research results that were carried out to optimize the fire extinguishment system of X Station in South Sumatera. To optimize the fire extinguishing system at station X, a system modification has been done, which included: changes in the number of stockpile tank units, changes in capacity and dimensions of oil tanks, and changes in fire wall construction. With the change in capacity and dimensions, especially the storage tank unit, it is necessary to recalculate whether the water demand in the fire protection system is still sufficient according to the existing system condition. From this research, it can be concluded that the maximum flow rate of foam under the existing condition is 1631.6 gpm while the optimum ondition is 65% smaller than the existing system condition at 570.54 gpm. The cooling water flow rate of 615.09 gpm at optimum ondition is lower than the existing system conditions of 1409.33 gpm. The required water to the fire extinguishment system is 250 gpm; this value is smaller than the existing system capacity of 2074 gpm. By using performance curves of Grundfos Data Booklet, for the capacity of pump 1250 gpm, the total head pump and pump efficiency are obtained 103.48 m and 77.5 %, respectively. Keywords: optimation; tank; water; foam; pump